Las manos en la masa - Tohme M.,María Consuelo; Córdova Pozo, Juana; Zapata Carpio, Cristóbal. 1968-; Kronfle Chambers, Roberto. 1970-; Bustamante, Judy. traductora (Edicuatorial, 2006)
La obra de Córdova presenta un lenguaje artístico internacional, cuyo pulso fue muy sentido en los años 90.